THE STUDY ON ISLAMIC VALUES AND WOMEN ENTREPRENEURSHIP MSMES - Asep Maksum; Lufthia Sevriana; Anggun Pratiwi; Asri Noer Rahmi (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2025)
This study investigates of Islamic values on the sustainability strategies of women-led, knowledge-based micro, small, and medium enterprises (MSMEs). Women entrepreneurs significantly contribute to community welfare, and to contextualize the analysis, this study employs a literature review approach by examining prior research on Islamic business ethics, gender dynamics in entrepreneurship, and sustainability practices in MSMEs. The review highlights how Islamic principles may serve as foundational values influencing sustainable business practices among women entrepreneurs. By using bibliometric analysis using data from the Scopus database spanning from 2005 to 2024. A total of 29 documents were initially identified using keywords related to Islamic values, women entrepreneurship, and MSMEs. The bibliometric data were analyzed using VOSviewer software to visualize publication trends, keyword networks, and research clusters in the field. Bibliometric analysis of 22 Scopus-indexed articles identified three dominant research clusters: Islamic ethics and gender identity, social capital and business knowledge, and community-based micro entrepreneurship. The Journal of Business Ethics was the most prominent outlet, and the most cited scholars were Essers & Benschop (2009). The results highlight a lack of empirical research connecting Islamic values with financial literacy and sustainability outcomes in women-led MSMEs. Islamic values, such as honesty, justice, and social responsibility, serve as ethical foundations for women entrepreneurs in Muslim contexts. Future studies should examine the link between Islamic womenpreneurs and financial literacy, particularly their engagement with Islamic microfinance. Additionally, exploring how cultural variations within Muslim societies influence women's entrepreneurial approaches would provide valuable insights.